Faktor yang Mempengaruhi Minat Menabung Pelajar SMAK - Maxymillianus Leo; Muhadjir Anwar (IPM2KPE, 2022)
This study aims to determine the factors that influence the interest in saving in SMAK Garum Seminary students, Blitar Regency. This research method is quantitative, this research is explanatory research. The population used in this study were students of SMAK Seminary Garum, Blitar Regency. The data analysis technique used in this research is PLS-SEMM using SmartPLS 3 for Windows 10 V3.2. and Microsoft Excel 2016. The results show that the financial literacy variable (X1) on the interest in saving (Y) has a path coefficients value of 0.842, and a P value of 0.000 < α = 0.05; b) the financial literacy variable (X1) on saving attitudes has a path coefficients value of 0.273, and a P value of 0.012 <α = 0.05; c) the subjective norm variable (X2) on the saving attitude variable (X3) has a path coefficients value of 0.473, and a P value of 0.000 < α = 0.05; d) the subjective norm variable (X2) on the interest in saving variable (Y) has a path coefficients value of -0.108, and a P value of 0.197 > α = 0.05; f) the saving attitude variable (X3) on the interest in saving (Y) has a path coefficients value of 0.207, and a P value of 0.011 < α = 0.05. In conclusion, financial literacy, saving attitudes, and subjective norms influence the intention to save. Keywords: Financial Literacy, Interest in Saving, Subjective Norm, Saving Attitude